Powder Mixed Dielectric in Electrical Discharge Machining of Inconel 718 / Said Ahmad...[et al.] - Ahmad, Said; Abd Rahim, Erween; Lajis, Mohd Amri; Ibrahim, Mohd Rasidi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Inconel 718 is one of the most difficult to cut material due to its, high hardness, high toughness, and poor thermal conductivity results in heat concentrated in the cutting zone, making it ineffective to be processed through conventional machining. So usually, an electrical discharge machining (EDM) is chosen in order to overcome such limitations. However, EDM is known as a slow machining process. Thus, by employing powder mixed in the dielectric fluid it is believe to enhance the machining efficiency. To achieve high performance in EDM for this research, higher peak current, Ip up to 40A, pulse duration, ton up to 400μs and powder concentration, Cp up to 4g/l were selected as the main parameters. Copper tungsten (CuW) was used as an electrode. The circulating dielectric system called High Performance EDM (HPEDM) was applied to conduct the experiment involving powder mixed dielectric. Their influence on the machinabilities of the material removal rate (MRR), and electrode wear rate (EWR), were experimentally investigated. The surface topography of the machined work piece and surface morphology of the electrode also have been observed. The results have shown that, at a highest Ip=40A and the lowest ton=200μs with Cp=4g/l yields the highest MRR. The improvement is almost 50% when comparing without powder concentration at the same parameter settings. In the case of EWR, lowest value of EWR was obtained at Ip=20A, ton=400μs and Cp=0g/l.